Development of Quasi‐Solid‐State Dye‐Sensitized Solar Cells Based on a Poly (vinyl alcohol)/Poly (ethylene glycol)/Functionalized Multi‐Walled Carbon Nanotubes Gel Electrolyte. Issue 2 (13th January 2017) - Khannam, Momina; Nath, Bikash Chandra; Mohan, Kiran Jyoti; Dolui, Swapan Kumar
Abstract: A series of quasi‐solid state dye sensitized solar cells (DSSCs) were fabricated with different wt % of carboxy functionalized multi walled carbon nanotubes (c‐MWCNTs) containing poly (vinyl alcohol)/poly (ethylene glycol) gel electrolyte. The structure and morphology of the polymeric gel electrolyte were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and energy dispersive X‐ray spectrum (EDX) analyses. The thermal stability of the polymeric gel electrolyte was evaluated by thermogravimetric analysis. Fabrication of the DSSCs were carried out by sandwiching the poly (vinyl alcohol)/poly (ethylene glycol)/ c‐MWCNT nanocomposite gel electrolyte in between the dye sensitized TiO2 photoanode and platinum‐based counter electrode. However, c‐MWCNTs forms network with channels of PVA/PEG matrix in gel electrolyte which reduces the charge transfer resistance (Rct ) of DSSCs, thereby significantly improving the photovoltaic properties of the DSSCs. The maximum photo conversion efficiency (η) of 3.5 % and short circuit current density (Jsc ) of 8.80 mAcm ‐2 was achieved using an optimum loading of 0.5 % c‐MWCNT. Abstract : A series of quasi‐solid state dye sensitized solar cells (DSSCs) were fabricated with different wt% of carboxy functionalized multi walled carbon nanotubes (c‐MWCNTs) containing poly (vinyl alcohol)/poly (ethylene glycol) gel electrolyte with commercially available TiO2 photoanode and platinum‐based counter electrode. The maximum photo conversion efficiency (η) of 3.5 % and short circuit current density (Jsc ) of 8.80 mAcm −2 was achieved using an optimum loading of 0.5 % c‐MWCNT.